The Influence of Product Quality, Price and Promotion on Purchase Decisions of Cosmetic Products in Sidoarjo: Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Produk Kosmetik di Sidoarjo - Saharani, Andina; Indayani, Lilik (Indonesian Journal of Innovation Studies, 2023)
Skincare is becoming a major necessity for women. With so many products circulating in Indonesia, it makes it difficult for women to choose according to their needs The purpose of this research was to determined The Effect of Product Quality, Price and Promotion on Purchase Decision of Emina Skincare Product in Sidoarjo. This research is a descriptive study using quantiative methods. The population in this research is woman who had used and buy Emina Skincare. Sampling using Non Probablity Sampling technique. The number of samples used is 80 respondents. The Data collected using quisionnaire method and the data analysis used is multple linier regression analysis using the SPSS Statistics version 22.The results of the study show and prove the influence of Product quality, price and promotion on the decision to purchase emina skincare in Sidoarjo partially and simultaneosly.